2016
DOI: 10.1186/s12887-015-0524-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of dairy intake of children and adolescents with different food and nutrient intakes in the Netherlands

Abstract: BackgroundDairy products are nutrient-rich foods that may contribute to adequate nutrient intakes. However, dairy intake might also be associated with other food sources that influence nutrient intakes. Therefore, we studied the association of dairy, milk and cheese intake with intake of foods and nutrients from (non)dairy sources.MethodsDietary intake was assessed from 2007 to 2010 through two non-consecutive 24-h dietary recalls in 1007 children (7–13 years) and 706 adolescents (14–18 years). Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
4
19
0
3
Order By: Relevance
“…Therefore, an unbalanced dietary pattern was observed for the studied population, as it presented a pattern with a high intake of energy, proteins, and fats and a low intake of carbohydrate and fiber. Regarding micronutrients, poorer nutritional adequacy was noted among the schoolchildren with inadequate calcium intake, similarly described by Campmans-Kuipers et al [ 29 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, an unbalanced dietary pattern was observed for the studied population, as it presented a pattern with a high intake of energy, proteins, and fats and a low intake of carbohydrate and fiber. Regarding micronutrients, poorer nutritional adequacy was noted among the schoolchildren with inadequate calcium intake, similarly described by Campmans-Kuipers et al [ 29 ].…”
Section: Discussionsupporting
confidence: 66%
“…We identified that children with adequate calcium intake have higher nutritional adequacy. Campmans-Kuijpers et al [ 29 ] similarly observed that children who had a high intake of one nutrient tended to have adequate intakes in the other nutrients. This possibly occurs due to the fact that eating patterns with high calcium content normally also have high vitamin and mineral contents.…”
Section: Discussionmentioning
confidence: 99%
“…Low intake of milk and other dairy products has been associated with carries among children [68]. Other comparable studies also similarly condemned that high intake of non-alcoholic carbonated drinks and low consumption of milk and other dairy products among children and adolescents increases the risk for dental caries and other systemic diseases [63,70,71]. Multiple studies reported that drinking milk ensures the consumption of many macronutrients and micronutrients which in turn promotes and protects health from various diseases [72,73,74].…”
Section: Nutrition Component That Promotes Dental Infectionmentioning
confidence: 99%
“…Since milk contains various essential vitamins and minerals with high bioavailability, consuming milk during adolescence is important for bone growth and general health promotion. Marjo et al [1] reported that the higher milk and dairy product consumption group was associated with lower consumption of non-alcoholic beverages such as soft drinks, tea, and coffee, and higher fruit and vegetable consumption in children and adolescents. It means that the consumption of milk and dairy product consumption may be a marker for good eating habits.…”
Section: Introductionmentioning
confidence: 99%